Strategy of Coniferous Needle Biorefinery into Value-Added Products to Implement Circular Bioeconomy Concepts in Forestry Side Stream Utilization - Klavins, Linards; Almonaitytė, Karolina; Šalaševičienė, Alvija; Zommere, Alise; Spalvis, Kaspars; Vincevica-Gaile, Zane; Korpinen, Risto; Klavins, Maris (MDPI AG, 2023)
Sustainable development goals require a reduction in the existing heavy reliance on fossil resources. Forestry can be considered a key resource for the bioeconomy, providing timber, energy, chemicals (including fine chemicals), and various other products. Besides the main product, timber, forestry generates significant amounts of different biomass side streams. Considering the unique and highly complex chemical composition of coniferous needle/greenery biomass, biorefinery strategies can be considered as prospective possibilities to address top segments of the bio-based value pyramid, addressing coniferous biomass side streams as a source of diverse chemical substances with applications as the replacement of fossil material-based chemicals, building blocks, food, and feed and applications as fine chemicals. This study reviews biorefinery methods for coniferous tree forestry biomass side streams, exploring the production of value-added products. Additionally, it discusses the potential for developing further biorefinery strategies to obtain products with enhanced value.
Keywords: picea; pinus; biorefinery; extraction; coniferous; needles; valorization; bioeconomy; resin